Taxonomic revision of the genus Morinda L. (Rubiaceae) in Bangladesh - Das, Sujit C; Rahman, M Atiqur (Bangladesh Journal of Botany, 2012)
The genus Morinda L. (Rubiaceae) has been revised for its species diversity in the flora of Bangladesh. The genus is represented by five species, viz., M. angustifolia Roxb., M. citrifolia L., M. persicaefolia Ham., M. pubescens Smith and M. umbellata L. Of these, M. pubescens Smith is a new record for Bangladesh. A key to the species with vernacular names, descriptions, illustrations, photographs, ecology, uses, geographical distribution and status of occurrence in the flora is provided. Key words: Taxonomy; Morinda; Rubiaceae; Bangladesh DOI: http://dx.doi.org/10.3329/bjb.v40i2.9766 Bangladesh J. Bot. 40(2): 113-120, 2011 (December)